Tertullian the African An Anthropological Reading of Tertullian's Context and Identities - Wilhite, David E. (Millennium-Studien / Millennium Studies, 2011)
This work is largely a social history of Tertullian, a Christian from Carthage (c.160 CE), and his ancient African context, which is viewed through a postcolonial lens.Theories from the discipline of social/cultural anthropology, e.g. kinship, class and ethnicity, are applied to selections of Tertullian`s writings.Some of the issues addressed include identity politics, Roman/African relations, martyrdom and the so-called Montanist heresy.